2004
DOI: 10.1074/jbc.m409175200
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Lactate Dehydrogenase Is Important for the Cell Cycle of Toxoplasma gondii

Abstract: In Toxoplasma gondii, lactate dehydrogenase is encoded by two independent and developmentally regulated genes LDH1 and LDH2. These genes and their products have been implicated in the control of a metabolic flux during parasite differentiation. To investigate the significance of LDH1 and LDH2 in this process, we generated stable transgenic parasite lines in which the expression of these two expressed isoforms of lactate dehydrogenase was knocked down in a stage-specific manner. These LDH knockdown parasites ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 33 publications
4
40
0
Order By: Relevance
“…Glycolysis has long appeared to be the main source of ATP and NAD(P)H in the erythrocytic stages of the malaria parasites, [5,[17][18][19][20][21]. Indeed, glucose uptake in P. falciparum-infected red blood cells (RBCs) has been observed to increase 75-100-fold compared to uninfected RBC [22][23][24][25].…”
Section: Plasmodium Falciparum and The Glycolytic Deceitmentioning
confidence: 99%
“…Glycolysis has long appeared to be the main source of ATP and NAD(P)H in the erythrocytic stages of the malaria parasites, [5,[17][18][19][20][21]. Indeed, glucose uptake in P. falciparum-infected red blood cells (RBCs) has been observed to increase 75-100-fold compared to uninfected RBC [22][23][24][25].…”
Section: Plasmodium Falciparum and The Glycolytic Deceitmentioning
confidence: 99%
“…Toxoplasma glycolytic genes function both in glycolysis and in other parasite processes such as parasite motility (7)(8)(9). These data led several groups to conclude that glucose was the primary carbon source that was scavenged by Toxoplasma from its host cell.…”
Section: Glucose and Glutamine Power The Parasitementioning
confidence: 99%
“…In T. brucei, a combination of efficient RNAi and a tight tet-regulated transcription is routinely applied for large scale analysis of genome function. In contrast, the efficiency of RNAi in apicomplexans is still a matter of debate [85,86], even if previous and more recent studies have reported the successful use of antisense/ribozyme in T. gondii [87][88][89] and some studies have suggested that the mechanism of RNAi can operate in the malaria parasites [90][91][92].…”
Section: Experimental Approaches and Tools Developed To Regulate Genementioning
confidence: 99%